ANALISIS ANTROPOMETRI PADA ANAK BALITA DAN FAKTOR-FAKTOR YANG BERKAITAN - Ila Fadila; Tutisiana Silawati; Eko Yuliastuti (Jurnal Matematika Sains dan Teknologi, 2008)
This study was conducted to explore the nutritional status of children under five factors (i.e. mother education background, family income, children under five healthy, health environment, access to health service, and access to media informations). A cross-sectional studybased on health service was conducted in Ciruas, Mancak, and Kramatwatu Serang, Banten. Analysis was done by observing on 121 peoples. The nutritional status of children under five was measured by using anthropometry. The conclusions there were 8% very poor nutritional status, 23% poor nutritional status, 64% good nutritional status, and 5% very good nutritional status. In general, for a very poor and poor nutritional status was dominated by mother with low educational background, frequency of feeding under three times a day, poor healt condition, limited access to media information, and poor environmental health. However, there are found that child with poor nutritional status in higher family income and mother with highest education background. It can be concluded that child nutritional status not only based on family income and mother educational background but also depend on the way of mother look after children under five.